Developing the capability of applying chemical knowledge to practice through study nitrogen and nitrogen fertilizer topics - Nguyen Thi Kim Anh; Chu Thi Nam (My University, 2018)
Developing the capability of applying chemical knowledge to practice through study nitrogen and nitrogen fertilizer topics
Keywords: Applying knowledge